2018
DOI: 10.1590/rbz4720170247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of STAT1, OLR1, CSN1S1, CSN1S2 , and DGAT1 genes on milk yield and composition traits of Holstein breed

Abstract: The objectives of the study were to evaluate allelic frequencies and test the association between STAT1, OLR1, CSN1S1, CSN1S2, and DGAT1 gene polymorphisms and milk production traits including lactation milk yield, 305 days milk yield, days before peak milk production, and peak milk yield. In addition, samples of milk were analysed for fat, protein, lactose, and total solid contents. A total of 168 purebred Holstein-Fresian cows were genotyped using polymerase chain reaction and restriction fragment length pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…Only few animals in the population were heterozygous. Similar results were obtained by Ardicli et al [ 9 ], who also investigated the same SNP and reported that in HF population most frequent was DD genotype (97.62% of all animals). Out of 168 tested animals, only four were heterozygous, having AD genotype.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Only few animals in the population were heterozygous. Similar results were obtained by Ardicli et al [ 9 ], who also investigated the same SNP and reported that in HF population most frequent was DD genotype (97.62% of all animals). Out of 168 tested animals, only four were heterozygous, having AD genotype.…”
Section: Resultssupporting
confidence: 89%
“…This may suggest that in the studied population one of the genotypes was favored during reproduction programs in the past. Other authors also described results of χ 2 test used to verify any deviation from H-W equilibrium, for instance, Ardicli et al [ 9 ] who investigated polymorphism in CSN1S1, noted that the tested HF population was not in H-W equilibrium (not all genotypes were present in the population, χ 2 was at the level of 0.42, and p -value at 0.52), similarly with CSN1S2 genotypes. Furthermore, Hristov et al [ 7 ] subjected their result to χ 2 test in order to evaluate the validity of H-W equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…In the study performed, the frequency of C allele was generally found high for the STAT1 gene in all populations as compared with T allele and the ratios of CC, CT, and TT genotypes were found as 53%, 40%, and 0.07%, respectively. In one of the recent studies, the frequencies of CC, CT and COBANOGLU, KUL, ABACI GURCAN, CANKAYA TT genotypes of the STAT1 gene were reported similarly in the same pattern but somewhat lower as 45.24% for CC, 36.31% for CT genotypes, but a little higher as 18.45% for TT genotype in Holstein cows raised in the other farm also located to west part of Turkey, respectively [20] . They reported that the population did not follow Hardy-Weinberg Equilibrium for this locus which might be due to sampling, inbreeding or population stratification.…”
Section: Discussionmentioning
confidence: 76%
“…Hamza et al (2011) reported that CN genotypes had significant effect on milk fat component. Previously, Ardicli et al (2018) reported that CSN1S1 genotypes were associated to milk fat. Besides, Dagnachew et al (2011) the genetic variants of CSN3 affected milk fat levels.…”
Section: Association Of Genetic Variants Of Milk Protein Genes On Milmentioning
confidence: 98%